The conceptual field of contemporary public diplomacy (Comillas Journal of International Relations, 2014)
This article considers public diplomacy as a distinct modality of diplomacy, arguing that it generally reflects the contemporary transformation of the international system and the ways of interacting and achieving influence within it. After identifying the main functions of diplomacy generally, the article considers the nature of the different public diplomacy modalities and how these fulfil diplomatic functions: Propaganda, national branding, strategic communication, relationship building and outsourced public diplomacy. Common to these are the challenges of actively listening to the audience and achieving a coherent and effective public diplomacy. Finally, the article argues that the power notions implied in public diplomacy are basically of an indirect and structural nature, permitting public diplomacy practices to add value to other, more classical, modalities of international interaction.
Keywords: public diplomacy; national branding; relationship building; power; diplomacy